The Ontogeny and Function of Placental Macrophages - Thomas, Jake R.; Naidu, Praveena; Appios, Anna; McGovern, Naomi (Frontiers in Immunology, 2021)
The placenta is a fetal-derived organ whose function is crucial for both maternal and fetal health. The human placenta contains a population of fetal macrophages termed Hofbauer cells. These macrophages play diverse roles, aiding in placental development, function and defence. The outer layer of the human placenta is formed by syncytiotrophoblast cells, that fuse to form the syncytium. Adhered to the syncytium at sites of damage, on the maternal side of the placenta, is a population of macrophages termed placenta associated maternal macrophages (PAMM1a). Here we discuss recent developments that have led to renewed insight into our understanding of the ontogeny, phenotype and function of placental macrophages. Finally, we discuss how the application of new technologies within placental research are helping us to further understand these cells.